(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The author suggests a method for drafting circling-point curves and centering-point curves of Burmester in the present paper. The geometrical compulsion makes the best use of synthesis of levers mechanisms by vector-matrix computer method under existing circumstances. Propose the drafting of the Burmester circling-point and centering-point curves are more applicable and more approach for engineers and constructors in the manufacture.